2012
DOI: 10.1155/2012/125890
|View full text |Cite
|
Sign up to set email alerts
|

Urine Metabolite Profiling of Human Colorectal Cancer by Capillary Electrophoresis Mass Spectrometry Based on MRB

Abstract: Aim. The study was to investigate the metabolic profile of urine metabolites and to elucidate their clinical significance in patients with colorectal cancer. Methods. Colorectal cancers from early stage and advanced stage were used in this study. Urine samples of colorectal cancer patients and healthy adults were collected and subjected to capillary electrophoresis mass spectrometry based on moving reaction boundary analysis. The metabolic data were analyzed by SPSS 17.0 to find urinary biomarkers for colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…20,21 Orna et al performed exhaled breath analyses of patients with different lung cancer pathologies and found that the composition of exhaled VOCs was different among these patients; in particular, the concentrations of the three compounds of 2-ethyl-1-hexanol, 1,3-dimethyl-benzene, and 1,3-bis(1,1-dimethylethyl)-benzene were significantly higher in patients with adenocarcinoma than in patients with squamous cell carcinoma. 22 Chen et al 23 examined four types of lung cancer, including adenocarcinoma, squamous cell carcinoma, bronchial carcinoid tumor, and non-small-cell lung cancer, and determined that different VOCs are exhaled by patients with different lung cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 Orna et al performed exhaled breath analyses of patients with different lung cancer pathologies and found that the composition of exhaled VOCs was different among these patients; in particular, the concentrations of the three compounds of 2-ethyl-1-hexanol, 1,3-dimethyl-benzene, and 1,3-bis(1,1-dimethylethyl)-benzene were significantly higher in patients with adenocarcinoma than in patients with squamous cell carcinoma. 22 Chen et al 23 examined four types of lung cancer, including adenocarcinoma, squamous cell carcinoma, bronchial carcinoid tumor, and non-small-cell lung cancer, and determined that different VOCs are exhaled by patients with different lung cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…20 In recent years, many investigations have focused on analyzing CRC by determining the urinary metabolic profiles, blood levels of water-soluble metabolites, and exhaled VOCs of CRC patients. 8,15,21 To the best of our knowledge, no study has investigated the specific volatile metabolic biomarkers that exist in the blood of CRC. Chen performed a metabolomics analysis of the effects of CRC on urine and determined that relative to the urine of a control group of healthy individuals, the urine of CRC patients exhibited significantly higher levels of lactic acid but lower levels of histidine and methionine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 It has been used for urinary and tissue metabolite profiling of CRC patients. 41,42 With the different advantages and limitations of NMR and MS techniques, multiple complementary analytical platforms are often utilized in order to maximize the spectrum of detectable metabolic changes associated with CRC. 36,43,44 In addition, metabolite elucidation and target quantification of metabolites of interest can also be performed by multiple analytical platforms.…”
Section: Sample Preparation and Instrumental Analysismentioning
confidence: 99%
“…The reduction of polyunsaturated ultra-long-chain fatty acids and the increase of long-chain fatty acids suggest the alteration of enzymes, such as fatty acid desaturases, which may be involved in the pathogenesis of CRC. The significance of one of the polyunsaturated ultra-long-chain fatty acids, [10,45,46] Fecal water biomarkers (analytical platforms: NMR)…”
Section: Metabolomic Profiling Studies In Crcmentioning
confidence: 99%